2010
DOI: 10.1007/s00467-009-1321-8
|View full text |Cite
|
Sign up to set email alerts
|

Captopril-enhanced renal scintigraphy in the diagnosis of pediatric hypertension

Abstract: Hypertension in childhood is no longer a rare condition mainly secondary to renal, or renovascular diseases, as a growing proportion of children are obese and hypertensive, with the phenotype of metabolic syndrome. Thus, we need to reconsider our practice in the examination of the hypertensive child and redefine the place of non-invasive methods for screening of renovascular hypertension, and specifically, to evaluate the value of captopril-enhanced renal scintigraphy at the two ends of the palette: the obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…391 -393 The utility of nuclear renography may be less in children then adults because children with RAS often have more complicated vascular abnormalities than adults. 394 Given these issues, nuclear renography has generally been abandoned as a screening test for RAS in children and adolescents. 390…”
Section: 8b Computed Tomographic Angiography Magnetic Resonance Anmentioning
confidence: 99%
“…391 -393 The utility of nuclear renography may be less in children then adults because children with RAS often have more complicated vascular abnormalities than adults. 394 Given these issues, nuclear renography has generally been abandoned as a screening test for RAS in children and adolescents. 390…”
Section: 8b Computed Tomographic Angiography Magnetic Resonance Anmentioning
confidence: 99%
“…Following a 4-week baseline, patients with gestational hypertension were randomized to a double-blind treatment with captopril, prazosin, combined therapy or placebo once daily. Although previous results indicated that treatment with captopril or prazosin was able to regulate the plasma concentrations of vasodilation-converting enzyme and α-adrenergic receptor, respectively (19,31), to the best of our knowledge, the clinical outcomes of combined captopril and prazosin have not been investigated in previous studies. Therefore, the present study aimed to evaluate the clinical application of combined treatment with captopril and prazosin.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, Van Guilder et al (30) have indicated that comprehensive effects of low-dose oral spironolactone and captopril therapy present more benefits for spontaneous hypertension and heart failure. Furthermore, Reusz et al (31) have recently suggested the influence of captopril treatment on occupational activity of engine operators with hypertension. These outcomes indicate that captopril is an efficient drug for the treatment of hypertension in preclinical and clinical experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The consequent dilatation lowers the glomerular transcapillary pressure, leading to a decrease in GFR. The decrease of the individual kidney GFR, induced by inhibition of ACE, can be evaluated by the captopril scintigraphy with the use of tubular agents, such as technetium-99m mercaptoacetyl triglycine (MAG3) or technetium-99m ethylenedicysteine (EC) or by glomerular agent, such as technetium-99m diethylene triamine penta-acetic acid (DTPA) 5 .…”
Section: Introductionmentioning
confidence: 99%